1990
DOI: 10.1088/0031-8949/41/1/003
|View full text |Cite
|
Sign up to set email alerts
|

Soft X-ray optics characterization on SURF II

Abstract: We describe the present capabilities and future plans for soft X-ray optics characterization at the NIST storage ring, SURF II. The existing facility is made up of a monochromator and a reflectometer capable of characterizing the reflectivity of soft X-ray devices, including multilayers, gratings and grazing incidence optics. This system can also be used to characterize the transmission of components such as filters. The present capabilities include a wavelength range from 80 Å to 600 Å. The reflectometer will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Spectral reflectivity measurements of the polarizers were performed at the SURF II beamline at NIST. 13 The results for two of the polarizers are shown superimposed with measurements of the undulator spectra in Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
“…Spectral reflectivity measurements of the polarizers were performed at the SURF II beamline at NIST. 13 The results for two of the polarizers are shown superimposed with measurements of the undulator spectra in Fig. 5.…”
Section: Resultsmentioning
confidence: 99%
“…The SURF II storage ring at NIST was used with a grazing-incidence grating monochromator and transmission filters to measure reflectance versus wavelength [8], with the incidence angle fixed to 10 degrees. Intensity measurements were made with a silicon photodiode, and were normalized to variations in the storage ring electron beam current by monitoring the flux incident to the monochromator.…”
Section: Methodsmentioning
confidence: 99%
“…The upper plot shows the measured and calculated reflectance versus incidence angle data at three wavelengths, while the lower plot shows the measured and calculated reflectance versus wavelength data. Best-fit calculated reflectances were computed using the optical constants from reference {11].1 Instrumental spectral resolutions were included in the calculations, and in the case of the NIST data, where the beam is highly polarized, the estimated incident beam polarization was also included [8]. For the Sandia laser-plasma measurements, a constant background (of order 5%) was subtracted from the data, to account for scattered light in this system.…”
Section: Methodsmentioning
confidence: 99%
“…Angle-resolved photoemission data were not conclusive [31]. Early energy-minimization calculations showed that buckled dimers were more stable [32], although total-energy calculations indicated that symmetric and asymmetric models had very similar energies at RT [33]. Ihm et al [25] performed total-energy calculations combined with position-space renormalization-group calculations to obtain predictions of the structural phase transitions of the Si(100) surface as a function of temperature.…”
Section: The C(4 × 2) ↔ (2 × 1) Phase Transition Of Si(001) and Ge(001)mentioning
confidence: 99%